### Present Remotely

Send the link below via email or IM

CopyPresent to your audience

Start remote presentation- Invited audience members
**will follow you**as you navigate and present - People invited to a presentation
**do not need a Prezi account** - This link expires
**10 minutes**after you close the presentation - A maximum of
**30 users**can follow your presentation - Learn more about this feature in our knowledge base article

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

### Make your likes visible on Facebook?

Connect your Facebook account to Prezi and let your likes appear on your timeline.

You can change this under Settings & Account at any time.

# Calculus

No description

by

Tweet## Sara Martinez

on 29 May 2013#### Transcript of Calculus

Chain Rule Calculus Derivatives Trig Functions Chain Rule f(x)=(4x+2)²

f'(x)=2(4x+2)(4)

f'(x)=8(4x+2) f(x)=2sin(4x-2)

f'(x)=2cos(4x-2)(4)

f'(x)=8cos(4x-2) Cosine Trig Function f(x)=cos(23x)

f'(x)=-sin(23x)(23)

f'(x)=-23sin(23x) f(x) = 1/u

f'(x) = 1(u^(-1))

f'(x) = -u F(x) = (f · g)(x)

(du/dx) f(g(u))=f'(g(u))g'(u)

dy/dx = (dy/du)(du/dx) Sine Trig Function Chain Rule f(x)=2(3x+5)²

f'(x)=2*2(3x+5)(3)

f'(x)=4(3x+5)(3)

f'(x)=12(3x+5) f(x) = f(g(x))²

f'(x) =2f(g(x))g'(x) f(x) = sin^-1u

f'(x) = 1/sqrt 1-u² Product Rule d/dx = u'(x)g(x) + u(x)g'(x) Exponential f(u) = e^u

f'(u) = e^u f(x) = Sin^-1(2x^3)

f'(x) = 1/sqrt 1-(2x)²(2)

f'(x) = 2/sqrt 1 - 2x²(2)

f'(x) = 2/sqrt 1 - 4x² Sin Inverse Trig Function

Full transcriptf'(x)=2(4x+2)(4)

f'(x)=8(4x+2) f(x)=2sin(4x-2)

f'(x)=2cos(4x-2)(4)

f'(x)=8cos(4x-2) Cosine Trig Function f(x)=cos(23x)

f'(x)=-sin(23x)(23)

f'(x)=-23sin(23x) f(x) = 1/u

f'(x) = 1(u^(-1))

f'(x) = -u F(x) = (f · g)(x)

(du/dx) f(g(u))=f'(g(u))g'(u)

dy/dx = (dy/du)(du/dx) Sine Trig Function Chain Rule f(x)=2(3x+5)²

f'(x)=2*2(3x+5)(3)

f'(x)=4(3x+5)(3)

f'(x)=12(3x+5) f(x) = f(g(x))²

f'(x) =2f(g(x))g'(x) f(x) = sin^-1u

f'(x) = 1/sqrt 1-u² Product Rule d/dx = u'(x)g(x) + u(x)g'(x) Exponential f(u) = e^u

f'(u) = e^u f(x) = Sin^-1(2x^3)

f'(x) = 1/sqrt 1-(2x)²(2)

f'(x) = 2/sqrt 1 - 2x²(2)

f'(x) = 2/sqrt 1 - 4x² Sin Inverse Trig Function